Gandouling ameliorates Wilson’s disease-associated liver fibrosis in mice with associated faecal microbiome and metabolome remodeling - Tang, Lulu; Dong, Wei; Liu, Danqing; Zhao, Chenling; Chen, Jie; Wen, Yuya; Zeng, Jingyu; Dong, Ting; Yang, Wenming (Frontiers in Pharmacology, 2025)
IntroductionIndividuals with Wilson's disease (WD) exhibit liver fibrosis, a basic pathological change that was recently demonstrated to be dynamic and reversible. The gut microbiota markedly influences the occurrence of WD. Gandouling (GDL), a standardized Chinese herbal formula, has demonstrated an anti-fibrotic effect against WD-associated liver fibrosis. We sought to determine whether GDL may prevent liver fibrosis in toxic milk (TX) mice by assessing its ability to regulate gut microbiota, metabolites, and barrier function.MethodsTX male mice aged 6 months were analysed. GDL was administered at varying doses over a 6-week period. The biochemical indexes related to liver function, fibrosis, and inflammation were determined using commercial assay kits. Histological analyses and immunohistochemistry staining, were performed to evaluate the histopathological changes and collagen deposition in mouse liver tissues. Additionally, to detect alterations in the intestinal bacterial composition and metabolites, faecal samples were examined using non-targeted metabolomics and 16S rRNA sequencing.ResultsThe administration of GDL demonstrated anti-fibrotic effects on the liver, decreased serum inflammatory markers, ameliorated liver histopathology, and restored ileal permeability in the model group, as compared to the control group. Furthermore, a medium dosage of GDL treatment significantly rebalance microbiota composition and function and modulated lipid and lipid-like molecule levels.DiscussionModulating intestinal homeostasis is a promising approach for treating liver fibrosis in patients with WD. Therefore, GDL may serve as a useful agent for treating WD-associated liver fibrosis.